MORNING SURGE AS PROGNOSTIC RISK FACTOR FOR TARGET ORGAN DAMAGE IN HYPERTENSIVE PATIENTS – DATA FROM A ROMANIAN UNIVERSITY-BASED HOSPITAL. (June 2018) - Varga, A.; Ardeleanu, E.; Suciu, C.; Tilea, I.
Abstract : Objective: Morning surge (MS), considered as a physiological pattern, still was identified as a risk factor for cardiovascular events in hypertensive patients. Previous studies confirmed that by increasing of target organ damage (TOD) in hypertensive patients there is an increase of total cardiovascular risk and mortality. Design and method: A descriptive, observational, cross-sectional study was performed on 160 hypertensive patients, fulfilling the inclusion criteria. The study was performed from January 2016 – February 2017 in patients admitted in a university-based hospital, in middle income area from Romania. For the accuracy of measurements ABPM was performed twice, for a minimum period of 24 hours using a BTL CardioPoint® ABPM equipment. Socio-demographic and biochemistry data were collected. Cardiac impairment was assessed by transthoracic echocardiography (Vivid E9 XD Clear, General Electric, Milwaukee, USA). Ankle – brachial index (ABI), as a marker of systemic atherosclerosis, was also assessed. Renal damage was quantified (eGFR – MDRD formula). Results: We included in our study 79 female, 81 males (mean age 63.3 + /- 11.7 y.o.) out of which ABPM data of 3 pts. were excluded for technical failure. A statistically significant correlation between systolic MS (>20 mmHg) and left ventricular hypertrophy (LVH) was computed out (p = 0.05). Neither renal impairment or vascular damage did not show a statistically significant correlation with pathological MS blood pressure rise. No statistically significant correlation was identified as trigger for MS rising above cut-off value for different c-v risk factors: gender (p = 0.49), age group (p = 0.43), smoking (p = 0.48), BMI (p = 0.19), diabetes mellitus (p = 0.15), total cholesterol (p = 0.77), triglycerides (p = 0.71). Conclusions: In hypertensive patients a 20 mmHg cut-off morning surge is associated with heart damage but same cut-off limit is not a sensitive predictive risk factor for chronic kidney disease. Extended studies could refine a more specific cut-off value of MS in different subsets of high risk patients. Targeted strategies to improve continuous 24 hours BP control may prevent cardiovascular morbidity and mortality.